Usefulness of hematopoietic progenitor cell monitoring to predict autologous peripheral blood stem cell harvest timing: A single-center retrospective study. (August 2021) - Kasane, Moemi; Kurosawa, Saiko; Kojima, Minoru; Iwashita, Nao; Kase, Yuki; Tsubokura, Misato; Nakabayashi, Saori; Ikeda, Chiaki; Kawamura, Kimihiko; Matsushita, Hiromichi; Narita, Ryuichi; Fukumoto, Hidetomo; et al.
Abstract: Introduction: In autologous peripheral blood stem cell harvest (APBSCH), CD34-positive cells have been measured to assess the numbers of hematopoietic stem cells, but measurement requires specialized equipment. Recently, there was a report that peripheral blood hematopoietic progenitor cells (HPCs) are useful indicators of the presence of hematopoietic stem cells. We examined the usefulness of HPC monitoring to predict APBSCH timing. Methods: We retrospectively analyzed the relationship between HPC and collected CD34-positive cells in 84 consecutive patients who underwent APBSCH. Results: According to the receiver operating characteristics curve for the collection of ≥2 × 106 CD34-positive cells/kg, the HPC cut-off value on the day before collection was 21/μL, while that on the day of collection was 41/μL. No significant factors were found in the univariate analysis except for the HPC count on the day before collection (p < 0.001) and the day of collection (p < 0.001). According to the multivariate analysis, the HPC count on the day before collection (p < 0.001) and the day of collection (p < 0.001) were also factors that strongly influenced the quantity of CD34-positive cells collected. Conclusion: Our results suggest that the HPC count on not only the day of collection but also the day before collection is a good indicator for appropriate APBSCH timing.